Effects of partial replacement of barley with rapeseed oil or birch wood in comparison to barley and oats on the performance and blood metabolites of lactating cows - Tesfa, Alem Tsehai; Tuori, Mikko; Syrjälä-Qvist, Liisa; Kaustell, Kaisa (Agricultural and Food Science, 1992)
Barley was partially replaced with either rapeseed oil (RSO), unextracted steamexploded birch wood (W1) or extracted steam-exploded birch wood (W2), and fed to 10 lactating cows (5 multiparous and 5 primiparous cows) in comparison to rolled barley and oats. The experiment was designed in two balanced 5x5 Latin squares. The experimental periods lasted for 4 weeks and the cows were fed with a fixed amount of 8 kg (air dry basis) concentrate in two equal portions. Timothy dominant unwilted grass silage was provided ad libitum. The nutrient digestibility, blood metabolites, milk yield and composition were studied. Grass silage intake decreased by replacing barley with RSO and increased with W 1 and W2. Oat feeding also increased silage intake compared to barley feeding. Oat feeding decreased the digestibility ofthe organic matter (OM) compared to barley. No significant difference was observed between diets in plasma concentrations of insulin, free fatty acids, acetoacetate, β-hydroxybutyrate and glucose. Replacing part of the barley with RSO increased milk yield by 1.3 kg and 0.87 kg compared to oats and barley feeding, respectively. Replacement of barley by low energy birch wood decreased milk yield. Both RSO and oat feeding decreased milk protein content. Milk urea concentration was elevated by oats and depressed by RSO and birch wood. RSO and oat feeding decreased the short chain fatty acid content of milk, with a concomitant increase in stearic and oleic acids.